Analisis SWOT Pada Penghimpunan Dana ZIS Online Di Lazismu Kota Medan - Suci Ardana; Sarwo Edi (Al-Sharf: Jurnal Ekonomi Islam, 2022)
This research has been carried out at LAZISMU Medan City, through the ZIS Fund Raising program. In this study, the researcher used a qualitative approach. The data presented in the form of a qualitative description in the form of reading so that to obtain accurate information, the researcher went directly to the field (field research). Data collection techniques used are observation, interviews, and documentation. The results of this study are applied to a SWOT analysis that LAZISMU Medan City should carry out socialization activities and educate the public about how to use digital applications, the lack of introducing programs will be a weakness in its management. And also several LAZISMU programs have become strengths to make it easier for people to make ZIS transactions anytime and anywhere.